Þ-Mangostin protects endothelial cell against H2O2-induced senescence via p38/Sirt1/MnSOD pathway - Kanjana Jittiporn, Jutima Samer, Piyanuch Thitiwuthikiat (Journal of Applied Pharmaceutical Science, 2024)
Cardiovascular diseases (CVDs) are a major cause of mortality. Increased CVD in ageing is associated with vascular endothelial dysfunction due to cell senescence, which is activated by oxidative stress. α-Mangostin is a pure substance from mangosteen (Garcinia mangostana L.) and has been shown to have antioxidant properties. However, the effect of α-mangostin on senescence in endothelial cells has not been widely studied. This study evaluated the effect of α-mangostin on H2O2-induced endothelial senescence. The concentrations of H2O2-induced senescent signalling and α-mangostin were determined by Western blot and 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) assays. Intracellular reactive oxygen species (ROS) production was determined by 2’, and 7’ dichlorodihydrofluorescein diacetate assay, and senescent cells were detected by β-galactosidase staining. Cell proliferation and nitric oxide (NO) production were determined by MTT and Griess assays. Senescent signalling was analyzed by Western blot. An H2O2 concentration of 50 μM was used to stimulate cell senescence. α-Mangostin doses of 0.1 and 1 μM were non-toxic and significantly reduced ROS formation and cell senescence, significantly increasing cell proliferation, mitochondrial membrane potential, and NO production. It significantly attenuated the phosphorylation of p38 MAPK and increased Sirt1 and MnSOD. This study found that α-mangostin suppresses oxidative stress and prevents H2O2-induced endothelial senescence by inhibiting p38 mitogen-activated protein kinase (MAPK) and stimulating Sirt1 and MnSOD.
Keywords: α-Mangostin, mangosteen, oxidative stress, senescence, H2O2, mitochondrial dysfunction